2017
DOI: 10.5539/ijsp.v6n3p109
|View full text |Cite
|
Sign up to set email alerts
|

Weighted Distributions: A Brief Review, Perspective and Characterizations

Abstract: The weighted distributions are widely used in many fields such as medicine, ecology and reliability, to name a few, for the development of proper statistical models. Weighted distributions are milestone for efficient modeling of statistical data and prediction when the standard distributions are not appropriate. A good deal of studies related to the weight distributions have been published in the literature. In this article, a brief review of these distributions is carried out. Implications of the differing we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Let us recall that the cdf of the OGWG distribution is defined by (1) with G(x) given (2). By noticing that odd G (x) = (e (βx) c − 1)/(1 − p), the corresponding cdf is given by…”
Section: Main Probability Functionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Let us recall that the cdf of the OGWG distribution is defined by (1) with G(x) given (2). By noticing that odd G (x) = (e (βx) c − 1)/(1 − p), the corresponding cdf is given by…”
Section: Main Probability Functionsmentioning
confidence: 99%
“…This limitation has triggered the creation of new families of distributions, often defined as compounding or weighting existing distributions. The most useful of them can be found in the surveys of [1,2]. In particular, the families of distributions defined with gamma generators has demonstrated a high ability to construct flexible models, showing nice fits for various kinds of real-life data sets.…”
Section: Introductionmentioning
confidence: 99%
“…Recent weighted exponential distributions with great ability in statistical applications include the exponentiated exponential (EE) distribution introduced by [9], the weighted exponential (WE) distribution introduced by [7], the Gamma exponentiated exponential (GEE) distribution introduced by [14], the weighted generalized exponential (WGE) distribution introduced by [10] and the exponentiated weighted exponential (EWE) distribution introduced by [13]. A brief review on weighted distributions (exponential or non-exponential) can be found in [15]. The statistical literature on proposing new weighted exponential distributions is vast and growing fast.…”
Section: Introductionmentioning
confidence: 99%
“…Further details on such family of distributions can be found in [19]. On the other side, [5] introduced the transmuted exponential distribution defined by the following cdf:…”
Section: Introductionmentioning
confidence: 99%